Turkish medical information system and medical librarianship - Güneş, Güssün; Çolaklar, Huriye; Yıldızeli, Aytaç; GÜNEŞ, GÜSSÜN (My University, 2010)
In Turkey, medical information is supported at state level according to national policies. However, although the history of medical libraries in Turkey goes back to the 13th century in Anatolia, modern medical library applications adopted since the 1950s have not received much state support. In the past thirteen years a few medical libraries joined forces under ÜNAK (the Association of University and Research Librarians) to contribute to the organization and development of Turkish Medical Information through the establishment of a "Medical Working Group" in 2000.
Keywords: medical information, medical librarianship, ÜNAK Medical Group, Turkish medical librarianship